Numerical Study of Density-Driven Convection in Laminated Heterogeneous Porous Media. (October 2020) - Li, Qian; Cai, Wei Hua; Li, Bing Xi; Chen, Ching-Yao
ABSTRACT: In the present study, we use direct numerical simulation to investigate the density-driven convection in a two-dimensional anisotropic heterogeneous porous media associated with significant laminated formation. At first, the heterogeneous porous media are randomly generated to represent laminated structure, in which the horizontal correlation length of permeability field is much longer than the vertical counterpart. Then, a highly accurate pseudo-spectral method and compact finite difference scheme with higher order of accuracy are employed to numerically reproduce the convection flow in the laminated porous media. The results show that the laminated structures restrict interactions among the downward plumes of heavier fluid. The plumes tend to descend more straightly in a laminated porous medium associated with a slower growth rate. As a result, the laminated distribution of permeability is considered having an inhibiting effect on the convection flow.